PERSEPSI ANGGOTA TERHADAP KINERJA BADAN USAHA MILIK DESA (BUMDES) SUMBER MAKMUR DI DESA KOTA BARU KECAMATAN KUNTO DARUSSALAM KABUPATEN ROKAN HULU - Viki Ade Maulana; Rosnita '; Eri Sayamar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Village’s corporation (BUMDes) is an institution that was builded by the village govermant that capital prosses and operational had efforted by the village govermant and society. The formed of BUMDes based on need and potential of village to increasingly the economics and build the village society social relations. Porpose of this researh are: (1) to analyze the effectiveness of BUMDes Sumber Makmur corporation based on members preceptions. (2) to analyze the efficient in using of resource by BUMDes Sumber Makmur Corporation based on members perceptions. (3) to know the sustainable BUMDes Sumber Makmur corporation based on members preceptions. The analyze of members preceptions to performance BUMDes corporation measuring by ordinal skale that is using the orientation on Likert’s Summated Rating Scale (LSRS), in every choices of answers gave the score. The research result showed that the preciptions of members to performance of BUMDes from the effectiveness variable corporation obtained skor 3,79 and it has included in the good category, efficiency variable in using of resource obtained skor 4,49, it has perfomed very well, and on the sustainable variable BUMDes Sumber Makmur corporation obtained skor 4,43, it also had included in very well category. Keyword: BUMDes, Effectiveness, Efficiency, Sustainability